The Effectiveness of Using an Arduino Uno Microcontroller-Based Radioactivity Detector as a Physics Learning Medium to Improve Students’ Scientific Literacy - Boisandi Boisandi; Nurussaniah Nurussaniah; Matsun Matsun (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze the effectiveness of using an Arduino Uno–based radioactive detector as a physics learning medium to improve students’ scientific literacy. The study employed a quasi-experimental method with a one-group pretest–posttest design, involving 30 students from the Physics Education Study Program, Faculty of Mathematics, Science, and Technology, Universitas PGRI Pontianak. The research instrument was a scientific literacy test consisting of five main indicators: explaining scientific phenomena, designing scientific inquiry, interpreting data and evidence, applying scientific concepts, and demonstrating scientific attitudes. Data were analyzed using the N-Gain score to measure improvement and a paired sample t-test to determine the significance of the difference between pretest and posttest results. The findings revealed an average N-Gain score of 0.366, categorized as moderate, indicating a noticeable improvement in students’ scientific literacy after learning with the Arduino Uno–based detector. The t-test results showed t = 14.97 and p = 0,356 × 10-15 (< 0.05), suggesting a statistically significant difference between pretest and posttest scores. These results demonstrate that the use of the Arduino Uno–based radioactive detector is effective in enhancing students’ scientific literacy, particularly in explaining scientific phenomena and interpreting experimental data.